Coca, Política y Estado el caso de Putumayo 1978-2006 (2012)
La presente investigación pretende contribuir a la discusión sobre Estado, política e ilegalidad. Con base en el estudio de caso de un departamento colombiano de la Amazonía occidental — Putumayo—, la investigación se pregunta por los efectos de la economía cocalera en la configuración local del Estado, en la política y en la articulación del territorio y sus habitantes con la sociedad nacional. Estas preguntas tienen implicaciones para la comprensión del tipo de ciudadanía que se construye en contextos de ilegalidad, así como para la conceptualización de los impactos de la coca en los diferentes órdenes políticos que se configuran en el país. / Abstract. This text focuses on Putumayo, a department in Colombia’s Amazon, a recently settled area with a regional economy that for the past three decades has revolved around illegal crops (1978-2008). It examines how the coca economy affects politics, local state-building, and the way the region ties in with national political life. It explores the role of the coca economy in local state-building in Putumayo. What kind of politics is encouraged in a place where the economy has revolved around illegal crops for three decades? How does the coca economy affect the local people’s relationship with the state, with national policy? Moreover, how are this region and the population linked to national policy?